Timothy Morton’s object-oriented ecology - Evandro Albiach Branco (Ambiente & Sociedade, 2025)
Abstract In Being Ecological, Timothy Morton expands on his proposal for a new ecology, structured upon object-oriented ontology and markedly detached from the concept of nature. For Morton, experiencing this ecology would require a radical transformation in our relationship with the world. The fundamental premises of this ecology are: (i) overcoming the subject-object duality through a flat ontological matrix, in which all objects-human and non-human, natural and cultural, real and fictional-possess the capacity to affect and be affected in a dynamic, unstable, and fluid process; and (ii) multiscalarity as an ontological condition. These conditions highlight that any form of access will always be partial and insufficient, as every object remains open and enigmatic in relation to its potential. This proposal for an ecological consciousness and stance suggests a radical ethical-political and epistemological shift, opening up thought-provoking avenues toward a new philosophy of the Earth System.